The Influence of Brand Ambassadors and Advertising on Purchasing Decisions at E-commerce Tokopedia - Masrurriana Elmiata; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
The goal of this study isbyo evaluate the advertisement and brand ambassadors impact to the purchasing decision on Tokopedia e-commerce. The method used is quantitative using non-probability sampling, namely purposive sampling. The population studied in this study were followers of the @7bts.update2 Instagram fanbase account. The sample consisted of 100 respondents selected implementing the formula slovin technique from the number of followers of the fanbase. The data were analyzed using SPSS 29 software, with descriptive techniques and multiple linear analysis to test hyphotesis. Results proves that 1) Brand ambassadors or commonly known through brand ambassadors provide a signficant and positive impact to the aspects of purchasing decision in Tokopedia e-commerce; 2) Advertising also provide a signficant and good impact to theaspects of purchasing decisions in Tokopedia e-commerce; 3) Simultaneously, brand ambassadors and the advertisement provide a signficant and good impact to the aspects of purchasing decisions in Tokopedia e-commerce. Both have an influence of 58.8%, when the 41.2% is impacted from some other factors not examined here.